Indolent NK cell proliferative lesion mimicking NK/T cell lymphoma in the gallbladder - Su Hyun Hwang; Joon Seong Park; Seong Hyun Jeong; Hyunee Yim; Jae Ho Han (Elsevier, 2016)
Natural killer (NK) cell-associated lymphoproliferative disorder includes NK/T cell lymphoma, nasal type and aggressive NK cell leukemia which exhibit poor outcomes. However, benign NK cell proliferative lesion has been recognized in the gastrointestinal tract under the name of NK-cell enteropathy or lymphomatoid gastropathy. We report a case of a similar CD56-positive NK-cell proliferative disorder involving the gallbladder and gastrointestinal tract in a 33-year-old woman who presented with chronic cholecystitis and underwent cholecystectomy. The gallbladder showed a few scattered polyps which were infiltrated by medium-sized atypical lymphoid cells with eosinophilic cytoplasmic granules. On immunohistochemistry, the lymphoid cells were positive for CD2, CD56, T-cell-restricted intracellular antigen-1, and granzyme B, but negative for CD3, CD4, CD5, CD8, CD20, CD30, CD34, CD68 and myeloperoxidase. In situ hybridization for Epstein-Barr virus-encoded RNA was negative and T-cell receptor gene rearrangement was polyclonal. The patient is under close observation for 36 months without any evidence of lymphoma.